2009
DOI: 10.1111/j.1469-185x.2008.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended phenotypes as signals

Abstract: Animal signals may result from construction behaviour and can provide receivers with essential information in various contexts. Here we explore the potential benefits of extended phenotypes with a signalling function as compared to bodily ornaments and behavioural displays. Their independence of the body, their physical persistence and the morphological and cognitive conditions required for their construction allow unique communication possibilities. We classify various levels of information transfer by extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 157 publications
(180 reference statements)
0
124
0
2
Order By: Relevance
“…The possibility that females signal their phenotypic quality to males through their nest building behaviors has only recently been considered, having previously been overlooked as it was thought that the expression of a certain amount of ornamentation in females could be explained as a genetically correlated result of sexual selection acting on males (Maynard Smith and Harper, 2003). Thus, empirical studies of female displays are relatively rare (Schaedelin and Taborsky, 2009) and this means that studies of female nest building behaviors in both blue and great tits (Broggi and Senar, 2009;Tomás et al, 2013) and other species (e.g., spotless starlings (Sturnus unicolor): Veiga and Polo, 2005; have significantly advanced our understanding of female displays more broadly. Pertinently, empirical studies have now convincingly demonstrated that the size and composition of female-built blue tit nests directly influences the parental care provided by their male partners and that such care determines both the number and quality of offspring raised (García-Navas et al, 2013;Tomás et al, 2013).…”
Section: Sexual Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that females signal their phenotypic quality to males through their nest building behaviors has only recently been considered, having previously been overlooked as it was thought that the expression of a certain amount of ornamentation in females could be explained as a genetically correlated result of sexual selection acting on males (Maynard Smith and Harper, 2003). Thus, empirical studies of female displays are relatively rare (Schaedelin and Taborsky, 2009) and this means that studies of female nest building behaviors in both blue and great tits (Broggi and Senar, 2009;Tomás et al, 2013) and other species (e.g., spotless starlings (Sturnus unicolor): Veiga and Polo, 2005; have significantly advanced our understanding of female displays more broadly. Pertinently, empirical studies have now convincingly demonstrated that the size and composition of female-built blue tit nests directly influences the parental care provided by their male partners and that such care determines both the number and quality of offspring raised (García-Navas et al, 2013;Tomás et al, 2013).…”
Section: Sexual Selectionmentioning
confidence: 99%
“…Intraspecific signaling between conspecifics usually consists of behavioral or physical signals such as elaborate songs, extravagant ornaments such as crests or long tails, or brightly colored plumages (Andersson, 1982). However, some species build structures that signal their phenotypic quality and whilst species such as bowerbirds build structures whose sole purpose is to attract a mate (Schaedelin and Taborsky, 2009), nests also contain eggs and/or offspring which suggests a direct trade-off between the conflicting requirements of natural and sexual selection (Sergio et al, 2011). For nest building behaviors to be extended phenotypic signals of the building individuals' quality, they must reliably indicate the quality of the builder by being associated with energetic costs (Nager and van Noordwijk, 1992;Maynard Smith and Harper, 2003;Moreno, 2012).…”
Section: Sexual Selectionmentioning
confidence: 99%
“…Phenotypes extended beyond the organism, so-called extended phenotypes, are changeable within and among individuals, populations or clades (Dawkins, 1982). Extended phenotypes are complex because multiple factors influence phenotypic expression (Schaedelin and Taborsky, 2009). Additionally, extended phenotypes not only adapt to the demands of the environment, they interact with it, modify it and gain feedback from it, thereby creating phenotype-environment interactions that flow through generations (Lehmann, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ants are known for marking a specific pathway on the ground with chemicals that signal to other members of the same species a track to follow. That track itself can be considered to be an extended phenotype (Schaedelin and Taborsky, 2009). Only members of the same species are able to recognize the chemicals in the track and to respond to them properly.…”
Section: Predictions and Conclusionmentioning
confidence: 99%